Reformas legales al art. 244 del código orgánico integral penal, relacionado a la no afiliación al Instituto Ecuatoriano De Seguridad Social en el Ecuador. - Morejón González, Roberto Eduardo (2015)
The Constitution of the Republic of Ecuador, states that everyone has the right to free access to justice and effective, impartial and expeditious protection of their rights and interests, subject to the principles of immediacy and speed of it in paragraph 29, paragraph c) of Article 66, establishes and guarantees the right to freedom stating that no person may be deprived of his liberty for debts, costs, fines, taxes, or other obligations, except for alimony. The supreme law in Article 34, guarantees the right to social security, noting that the right to social security is an inalienable right of all persons, and shall be the duty and responsibility of the state primary. Social security will be governed by the principles of solidarity, obligation, universality, equity, efficiency, subsidiarity, adequacy, transparency and participation, to the attention of the individual and collective needs. It further provides that the State shall guarantee and make effective the exercise of the right to social security, which includes individuals who perform unpaid work in households, activities for self-sustenance in the field, all forms of self-employment and those are unemployed; however, is the same Ecuadorian State is failing by not providing high quality services with respect to social security, as the member for treatment must do so by telephone, delay days and months in attaining long-awaited health care. Recently, through the issuance of the Code Comprehensive Criminal is criminal offense, non-membership to the Ecuadorian Institute of Social Security workers as employees and in Article 244 ibid, provides that the or employer not enroll their workers to compulsory social insurance within thirty days from the first day of work, shall be punished with imprisonment of three to seven days, a provision that is extreme and inconsistent with the provisions of the Constitution, which guarantees the right to freedom, effective protection and legal security of all people. In this regard and in order to protect the aforementioned rights, I consider that Article 244 of the Penal Code of Integral merits an urgent legal reform, replacing the sentence of preventive detention for a pecuniary penalty or fine. Under this provision if it is true, the National Assembly issued the Code of Integral Criminal same as for other sanctioned discriminatory breach of the no affiliation to compulsory social insurance, as when an individual is deprived of liberty as Art. 244 of COIP, and is a legal person is punished monetarily and with the intervention of the company pursuant to Art. 243 ibid, this implies different penalties for the same offense.